High detection rate for disease-causing variants in a cohort of 30 Iranian pediatric steroid resistant nephrotic syndrome cases - Najafi, Maryam; Riedhammer, Korbinian M.; Rad, Aboulfazl; Torbati, Paria Najarzadeh; Berutti, Riccardo; Schüle, Isabel; Schroda, Sophie; Meitinger, Thomas; Ćomić, Jasmina; Bojd, Simin Sadeghi; Baranzehi, Tayebeh; Shojaei, Azadeh; et al. (Frontiers in Pediatrics, 2022)
Background: Steroid-resistant nephrotic syndrome (SRNS) represents a significant renal disease burden in childhood and adolescence. In contrast to steroid-sensitive nephrotic syndrome (SSNS), renal outcomes are significantly poorer in SRNS. Over the past decade, extensive genetic heterogeneity has become evident while disease-causing variants are still only identified in 30% of cases in previously reported studies with proportion and type of variants identified differing depending on the age of onset and ethnical background of probands. A genetic diagnosis however can have implications regarding clinical management, including kidney transplantation, extrarenal disease manifestations and in some cases even causal therapy. Genetic diagnostics therefore play an important role for the clinical care of SRNS affected individuals. Methodology and Results: Here, we performed NPHS2 Sanger sequencing and subsequent exome-based genetic screening in 30 consanguineous Iranian families with a child affected by SRNS with a mean age of onset of 18 months. We identified disease-causing variants in 22 families (73%), including variants in NPHS1 (30%), followed by NPHS2 (20%), WT1 (7%) as well as in NUP205, COQ6, ARHGDIA, SGPL1 and NPHP1 in single cases. Eight of these variants have not previously been reported as disease-causing, including four NPHS1 variants and one variant in NPHS2, ARHGDIA, SGPL1 and NPHP1 each. Conclusion: In line with previous studies in non-Iranian subjects, we most frequently identified disease-causing variants in NPHS1 and NPHS2. While Sanger sequencing of NPHS2 can be considered as first diagnostic step in non-congenital cases, the genetic heterogeneity underlying SRNS renders next-generation sequencing based diagnostics as the most efficient genetic screening method. In accordance with the mainly autosomal recessive inheritance pattern, diagnostic yield can be significantly higher in consanguineous than in outbred populations.